Penggunaan Model Cooperative Learning dalam Meningkatkan Kemampuan Berpikir Kritis Peserta Materi Elastisitas dan Hukum Hooke - Wattimury, Reico; Kereh, Cicylia Triratna; Jamaludin, Jamaludin (Pattimura University, 2025)
This study aims to improve students' critical thinking skills in Elasticity and Hooke's Law. The research type is quantitative descriptive with a one-group pretest-posttest design. The research population consists of 50 students in grade XI MIA, while the sample was determined using judgment sampling, resulting in grade XI MIA-1 with 25 students. Data were collected using a test method in the form of test questions and a non-test method in the form of Student Worksheets (LKPD). Data were analyzed descriptively and quantitatively based on critical thinking ability indicators, and the increase was calculated using the N-Gain test. The results showed that before the intervention, students' critical thinking ability was at a very low level. After the implementation of cooperative learning, critical thinking skills improved to a high level. The N-Gain test also showed a significant improvement in students' critical thinking skills. Thus, the use of the cooperative learning model can serve as an alternative teaching strategy to enhance critical thinking skills and is expected to serve as a reference for teachers in their efforts to improve the quality of physics education.